Use of employments on swimming in pulling in and restoration microcycles in the training process of the highly skilled sportsmen of the highly skilled heavy weight sambo wrestlers - I.P. Zakorko (Physical Education of Students, 2013)
Expedience of the use of the sporting and health swimming is grounded in precontest preparation of the highly skilled sportsmen unarmed self-defence. 10 sportsmen took part in research (weight over 90 kg). Offered to recommendation on the use of swimming in renewal of sportsmen after the competition and trainings loadings. On employments, swimming was utillized a method crawl on a breast and by a method breast-stroke. Length of path of pool is 25 meters. The level of influence of trainings is set on swimming of different orientation on the general consisting of the sportsman unarmed self-defence of context of preparation and renewal during the specialized competition activity. It is recommended in training on swimming to utillize overcoming at full pelt of cutting-off 250 meters in the mode to 5 minutes (time of competition fight is in the fight of sambo-5 of minutes).